Odpowiedzi

2010-04-12T16:28:05+02:00
2x -3y =7 /*(-3)
3x - 5y =11 /*2

-6x+9y=-21
6x-10y=22

-y=1 /(-1)
y=-1

2x-3(-1)=7
2x+3=7
2x=4 /2
x=2

x=2
y=-1



2)
6( 3x + 1 ) +2 ( y-3 ) =2
2x + 3y = 3

18x+6+2y-6=2
2x+3y=3

2y=2-18x
2x+3y=3

y=1-9x
2x+3y=3

y=1-9x
2x+(1-9x)=3

y=1-9x
2x+1-9x=3

y=1-9x
-7x=2

y=1-9x
x=-2/7

y=1-9*(-2/7)
x=-2/7

y=1+18/7
x=-2/7

y=3 i 4/7
x=-2/7
2010-04-12T16:30:20+02:00
2x -3y =7 | razy (-3)
3x - 5y =11 | razy 2

-6x+9y= -21
6x-10y=22

-y=1 | :(-1)
y= -1

-6x+9y=-21 | razy10
6x-10y=22 |razy9

-60x+ 90y= -210
54x-90y=198

-6x=-12 | :(-6)
x= 2





6( 3x + 1 ) +2 ( y-3 ) =2
2x + 3y = 3

18x+6+2y-6=2
2x+2y=2

18x+2y=2-6+6
2x+2y=2

18x+2y=2 | razy (-1)
2x+2y=2 | razy 9

-18x-2y=-2
18x+18y=18

16y=16 | :16
y=1

18x+2y=2 | razy (-1)
2x+2y=2

-18x-2y=-2
2x+2y=2

-16x=0
2010-04-12T16:33:21+02:00
2x -3y =7|*3
3x - 5y =11|*(-2)< --- Metodą przeciwnych współczynników

6x-9y=21
-6x+10y=-22
y=-1

2x-3*(-1)=7
2x+3=7
2x=4
x=2

spr:
2x -3y =7
2*2-3*(-1)=7
4+3=7
7=7




6( 3x + 1 ) +2 ( y-3 ) =2
2x + 3y = 3 <---- Metodą podstawiania <---- Metodą podstawiania

18x+6+2y-6=2
2x+3y=3

18x+2y=2|:2
2x+3y=3

y=1-9x
2x+3(1-9x)=3
2x+3-27x=3
-25x=0
x=0

y=1-9*0
y=1-0
y=1

spr:
2x + 3y = 3
2*0+3*1=3
0+3=3
3=3
1 5 1